The dynamics of accounting practices and accountability in the selected mosques in federal territory - Siti Rokyah Md Zain,; Ros Norita Abdul Samad,; Mohamed Muneer Samsudin,; Raduan Noor Armia, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The aim of the paper is twofold. First, it describes the accounting practices at the selected mosques in Federal Territory in Malaysia. Second, it reviewed the financial records provided by the mosque committee members to portray their accountability. Within a three-month period, the study employed a series of unstructured interviews with key leaders of the four selected mosques such as the imams, mosques chairman, mosque treasurers and account clerks. It also reviewed some of the financial records of particular mosques such as financial statements, Friday’s collection statements and other accounting-related records. In addition, researchers also observe the counting of Friday collection of three mosques. The finding suggests that accounting is dynamic in meeting the needs of mosque committee members to demonstrate their accountability and as part of their day-to-day activities. It is also discovered that the mosques committee members perceived that accounting practices are imperative tools to support various activities carried out by the mosques. As accounting is loosely practice by the selected mosque, it provides the wisdom of accountability for the four mosques that vary from one another since accounting practices and accountability are based on the wisdom of the committee members of the mosques.